Internalization of scouting values in social sciences learning as an effort to form student character - Rahmatullah, Rizka; Bahtiar, Bahtiar; Zahrawati B, Fawziah; Herawaty, Hasmiah; Jumaisa, Jumaisa (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2023)
Character degradation is an issue that has not yet found an end point in the world of education. Various efforts have been made to overcome this problem, one of which is by utilizing extracurricular scout activities. This research aims to determine the internalization of scouting values in social studies learning as an effort to build student character. Using a qualitative approach, this research was at MTs.Negeri 2 Sidrap. Research informants were school principals, teachers, and students. Data collection techniques are in-depth interviews, observation, and documentation. To obtain the validity of the data, triangulation of methods and sources was carried out. After the data was collected, the data was analyzed by referring to the stages of Miles and Huberman. The results of the research found that efforts to shape students’ character through scouting extracurricular activities will involve habituation, role modeling, sanctions, and are expected to shape students’ personalities into discipline. The process of internalizing scouting values is taught and instilled by students or scout members through the 10 pillars of character formation in Dasa Dharma and instilled in students such as devotion to God Almighty, willingness to help and be steadfast, pure in thoughts, words and deeds, as well as a high sense of responsibility.